Employee Performance Evaluation Using the Standard Method of Deviation Multi-Objective Optimization by Ratio Analysis - Isnain, Auliya Rahman; Rahmanto, Yuri (PT. Tech Cart Press, 2024)
Employee performance refers to the extent to which an employee can achieve the goals and expectations that have been set by the organization, both in terms of quantity and quality of work. Employee performance appraisals cover various aspects, such as productivity, skills, discipline, creativity, and the ability to adapt to change. The main problem in employee performance evaluation is often related to the accuracy of assessments of various aspects of performance. Employee performance appraisal is a systematic process to evaluate the extent to which an employee meets the standards set by the organization in carrying out his or her duties and responsibilities. The purpose of this study is to apply the SD-MOORA method in evaluating employee performance objectively and comprehensively in the evaluation process, improve the accuracy of assessment, and provide a clearer picture of employee performance based on relevant criteria. The results of employee performance evaluation using the SD-MOORA method show that Siti Aisyah and Dina Putri occupy the top position with the same preference value, which is 0.47715, which indicates that their performance is superior in meeting the evaluation criteria. Both of these employees demonstrated consistent performance across the various aspects measured. In second place, there is Ahmad Firdaus with a preference score of 0.42932, which also reflects a fairly good contribution, although slightly lower than the two employees in the first rank. These results provide guidance for management to identify the best performing employees as well as design appropriate development strategies for other employees to increase their contributions in the future.